2010
DOI: 10.1016/j.cub.2010.11.040
|View full text |Cite
|
Sign up to set email alerts
|

Parallel Reinforcement Pathways for Conditioned Food Aversions in the Honeybee

Abstract: SummaryAvoiding toxins in food is as important as obtaining nutrition. Conditioned food aversions have been studied in animals as diverse as nematodes and humans [1, 2], but the neural signaling mechanisms underlying this form of learning have been difficult to pinpoint. Honeybees quickly learn to associate floral cues with food [3], a trait that makes them an excellent model organism for studying the neural mechanisms of learning and memory. Here we show that honeybees not only detect toxins but can also lear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
233
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(244 citation statements)
references
References 41 publications
9
233
1
1
Order By: Relevance
“…Areas in the crab brain that are structurally homologous to the mushroom bodies of insects receive dopaminergic innervations and undergo plasticity related with the contextual aversive memory (7). In addition, it was shown that dopaminergic neurotransmission is necessary during aversive training to elicit formation of aversive long-term memory in crabs, as in honey bees and crickets (2,3,7,16). We found that injection of dopamine coincident with appetitive training impairs formation of long-term appetitive memory in crabs and in honey bees (7,9).…”
Section: Mutual Interference Between Appetitive and Aversive Memoriesmentioning
confidence: 71%
See 1 more Smart Citation
“…Areas in the crab brain that are structurally homologous to the mushroom bodies of insects receive dopaminergic innervations and undergo plasticity related with the contextual aversive memory (7). In addition, it was shown that dopaminergic neurotransmission is necessary during aversive training to elicit formation of aversive long-term memory in crabs, as in honey bees and crickets (2,3,7,16). We found that injection of dopamine coincident with appetitive training impairs formation of long-term appetitive memory in crabs and in honey bees (7,9).…”
Section: Mutual Interference Between Appetitive and Aversive Memoriesmentioning
confidence: 71%
“…Studies in honey bees have addressed memory after training in which the same odor is associated with simultaneous appetitive and aversive consequences (15,16). The result that bees did not evidence appetitive memory toward the learned odor is interpreted as a consequence of an interaction between opposite reinforcements.…”
mentioning
confidence: 99%
“…The authors concluded that this was a post-ingestive response, as nicotine failed to stimulate the caterpillars' gustatory receptors, and taste-mediated aversive responses would have been faster in this species (Glendinning, 1996). In honeybees, in addition to gustatory responses to toxins, a post-ingestive mechanism involving serotonin has been identified as playing a role in conditioned food aversions (Wright et al, 2010). It is therefore possible that honeybees may have used post-ingestive mechanisms to detect the nectar nicotine in our study.…”
Section: Feeding Response To Nectar Nicotinementioning
confidence: 77%
“…Accumulating evidence, however, suggests that honeybees are indeed able to detect secondary metabolites Singaravelan et al, 2005;Wright et al, 2010), and their taste perception is likely to be more complex than assumed from the number of gustatory receptors (de Brito Sanchez et al, 2007 Wright et al (2010) have recently shown that gustatory receptors on the proboscis do respond to such substances. Honeybees are less likely to drink sucrose-quinine solutions presented to the proboscis as the toxin concentration increases (Wright et al, 2010).…”
Section: Feeding Response To Nectar Nicotinementioning
confidence: 99%
“…This assay of food consumption described by Tiedeken et al 7 revealed that bees can detect bitter compounds in solutions. However, this assay was unable to distinguish taste from post-ingestive processes such as malaise that could also affect feeding behavior over this time interval [8][9][10] .…”
Section: Introductionmentioning
confidence: 99%